Credit Reporting and Financing Constraints - Love, Inessa (World Bank, Washington, DC, 2014)
The authors combine firm-level data from the World Bank Business Environment Survey (WBES) with data on private and public credit registries to investigate whether the presence of a credit registry in a country is associated with lower financing constraints, as perceived by managers, and with higher share of bank financing. They find that the existence of private credit registries is associated with lower financing constraints and higher share of bank financing, while the existence of public credit registries does not seem to have a significant effect on these perceived financing constraints. The authors also find that small- and medium-sized firms tend to have a higher share of bank financing in countries where private registries exist and stronger rule of law is associated with more effective private credit registries. Finally, the authors find some evidence that the presence of a public credit registry benefits younger firms relatively more than older firms.